Circular orbits and collisions of particles with magnetic dipole moment around magnetized Bocharova–Bronnikov–Melnikov–Bekenstein black holes - Nuriddin Kurbonov; Ashfaque H. Bokhari; Javlon Rayimbaev; Bobomurat Ahmedov (European Physical Journal C: Particles and Fields)
Abstract In this study, we investigate the motion of magnetized particles around a Bocharova–Bronnikov–Melnikov–Bekenstein (BBMB) black hole in an external magnetic field, emphasizing the effects of an external magnetic field and a conformally coupled scalar field. We analyze the properties of circular orbits, the innermost stable circular orbit (ISCO), and the dynamics of high-energy particle collisions, focusing on the center-of-mass energy (CME) of colliding particles. We derive the equations governing the motion of magnetized particles in the BBMB spacetime and explore how the scalar coupling and the magnetic-dipole interaction parameters influence orbital stability and collision energetics. Our findings reveal that the ISCO radius is significantly modified by both scalar and magnetic interactions, leading to shifts in stability conditions and variations in the angular momentum requirements. The study also demonstrates that the critical angular momentum, which determines the transition between bound and unbound motion, is reduced compared to the Schwarzschild case due to the influence of the conformal scalar field. One key result is that the CME of colliding magnetized particles can be significantly enhanced in the BBMB spacetime. Increasing magnetic interaction and a stronger attractive scalar field lead to higher CME values, making the BBMB black hole a potential site for high-energy astrophysical processes. This suggests that external magnetic fields and scalar interactions play a crucial role in energy extraction mechanisms and the formation of ultrarelativistic particles.